2016
DOI: 10.5194/acp-16-4401-2016
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Development of chemoinformatic tools to enumerate functional groups in molecules for organic aerosol characterization

Abstract: Abstract. Functional groups (FGs) can be used as a reduced representation of organic aerosol composition in both ambient and controlled chamber studies, as they retain a certain chemical specificity. Furthermore, FG composition has been informative for source apportionment, and various models based on a group contribution framework have been developed to calculate physicochemical properties of organic compounds. In this work, we provide a set of validated chemoinformatic patterns that correspond to (1) a compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 91 publications
3
58
0
Order By: Relevance
“…Only relative metrics are used as Sax et al (2005) reported measurements in mole fractions of FGs, and the simulations do not include wall losses of particles and SVOCs that affect overall estimates of yield. Neglecting compound-specific SVOC deposition to walls may further incur biases in relative compositions as raised by Ruggeri et al (2016), but for this conceptual study we neglect its effect as its parameters are not precisely known.…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Only relative metrics are used as Sax et al (2005) reported measurements in mole fractions of FGs, and the simulations do not include wall losses of particles and SVOCs that affect overall estimates of yield. Neglecting compound-specific SVOC deposition to walls may further incur biases in relative compositions as raised by Ruggeri et al (2016), but for this conceptual study we neglect its effect as its parameters are not precisely known.…”
Section: Data Setmentioning
confidence: 99%
“…Furthermore, this approach allows development of parameterizations to more precisely estimate the organic carbon content from measured FG abundance. We use simulated photooxidation products of α-pinene secondary organic aerosol previously reported by Ruggeri et al (2016) and FG measurements by Fourier transform infrared (FT-IR) spectroscopy in chamber experiments by Sax et al (2005) to infer the relationships among molecular composition, FG composition, and metrics of organic aerosol functionalization. We find that for this simulated system, ∼ 80 % of the carbon atoms should be detected by FGs for which calibration models are commonly developed, and ∼ 7 % of the carbon atoms are undetectable by FT-IR analysis because they are not associated with vibrational modes in the infrared.…”
mentioning
confidence: 99%
“…1710 -1680 Aromatic polycarboxylic acids (C=O) [12] 1706 C=O in aldehydes and ketones [55] 1700 Carbonyl (C=O) [54] 1690 -1680 Hydrogen bonded (O-H) [8] 1680 -1665, 1660 -1630 Aliphatic hydrocarbons (C=C) [12] 1680 -1630 C=O stretch in amide [44] 1680 -1620 Unsaturated aliphatic (C=C) [48] 1650 -1620 Alkenyl double bond stretch (C=C) [10] 1650 -1590 Amino (C-NH 2 ) [48] 1644, 1281, 849 O-N groups [31] 1640 -1560 N-H bend in primary amines [44] 1640 -1550 Primary and secondary amide N-H bend [44] 1440 -1220 Alcohol and phenol (C-O-H bend) [44] 1400 -1390 C-H deformation of CH 3 groups [52] 1400 OH in carbohydrates [12] 1400 C-H in carbohydrates [12] 1350 -1340 Nitro-aromatic (NO 2 ) [42] 1350 -1000 C-N stretch in amines [44] 1340 -1250 Aromatic (C-N) [48] 1320 -1210 Aliphatic carboxylic acids (CO) [12] 1320 -1210 Amino acids/Amines (CO) [12] 1300 -1100 Ketone C (C=O)C bend [44] 1300-1000 C-O stretch in ether, ester [44] 1298 -1200 Organonitrates [46] 1286, 1249, 1222 -CH 2 wagging [50] 1280 Organonitrate [41] 1280 -1278, 1631 Organonitrate [53] 1280 -1270 Organonitrate (ONO 2 ) [42] 1280 -1210 Esters/ethers/phenols (C-O) [7] 1280 -1137 C-O stretching of esters, ethers and phenols [52] 1280 Symmetric NO 2 stretch in organonitrate [44] G. 1260 -700 Alkane skeletal vibration (C-C) [38] 1220 C-O stretching and O-H bending vibrations of COOH [5] 1210 -1160, 1100 -1030 Esters/Lactones (C-C-O) [12] 1200 -900 Carbohydrates (C-O-C) [12] 1182 C-O-C stretching …”
Section: Ftir Spectral Interpretations For Characteristic Groups In Omentioning
confidence: 99%
“…A comprehensive interpretation of FTIR spectra has been tabulated in Aliphatic carboxylic acids (OH) and Amino acids/Amines (OH) [12] 3500 -2500 Carbohydrates (C-OH) [12] 3500 -3100 Organic hydroxyl (C-OH) [19] 3440 -3400 Hydroxyl (-OH) [30] 3400 -2500 Carboxylic acid (OH) [45] 3400-2400 Carboxylic acid (OH stretch) [24] [ 44] 3400, 1440 -1220, 1260 -1000 Alcohol and phenol [44] 3400, 1625 Amine (NH 2 ) [19] [20] 3400 OH stretching of phenol hydroxyl and carboxyl [5] 3382 -3323 Alcohol (OH) [45] 3380 H-bonding of hydroxyl [46] 3350, 1350, 650 ± 50 Alcohols/Phenols (OH) [12] 3350 -3205 Alcohol COH [24] 3350, 3180 Primary amide N-H stretch [44] 3300 -3150 Alcohol groups [33] 3300 -2900 C-H stretching in alkane, alkene, alkyne, aromatic [44] 3300 Secondary amide N-H stretch [44] 3300 Hydrogen bonded [8] 3200 -3000, 1290 -1000 Aromatic carbon (Arom-H) [38] G. 3200 -3000 Aromatic carbons (Arom-H) [36] 3130 -3030, 900 -670 Aromatic (C=C-H) [48] 3100 -3070 Carboxylic acid (COOH) [30] 3100 -3000 Aromatic (C-H) [42] 3100 -2900 Unsaturated aliphatic (C=C-H) [17] [19] [20] 3100 -3000 Alkene (C-H) [38] 3100 -3000 Aromatic (C=C-H) [17] [19] [20] 3100 -3000 Unsaturated aliphatic (C=C-H) [48] 3100 -3000 Unsaturated and aromatic (C-H) [12] 3100 H-bonding of organic acid [46] 3100 -2900 Alkane groups [33] 3090 -3075, 3050 -3000, 990 -815 Aliphatic Hydrocarbons (C-H) [12] 3050 Aromatic (C-H) [24] [ …”
Section: Ftir Spectral Interpretations For Characteristic Groups In Omentioning
confidence: 99%
“…When particulate matter samples are analyzed directly, the totality of OA can be characterized. OA is described by FT-IR analysis as the sum of organic functional groups, i.e., alkyl (C-H) bonds, carbonyl (C=O), carboxyl (C(OH)=O), amine (NH), hydroxyl (C-OH) groups, organic sulfate, and organic nitrate (Russell et al, 2011;Ruggeri and Takahama, 2016). Time resolution is limited by the detection limit and ambient OA concentrations.…”
mentioning
confidence: 99%